Inelastic seismic energy spectra for soft soils: Application to Mexico City. Issue 89 (October 2016) - Quinde, Pablo; Reinoso, Eduardo; Terán-Gilmore, Amador
Abstract: Earthquake databases are not sufficiently complete, particularly for soft soils. Also, there are few and oversimplified formulations that allow an understanding on the relation that exists between the elastic and inelastic energy demands for this type of soils. A study on energy reduction factors aimed at establishing inelastic input and hysteretic energy spectra for narrow-banded motions is presented. Unlike previous works, in this study elastic input energy spectra are used as input for energy functional forms that allow the formulation of inelastic energy spectra. For this purpose, over 250 seismic records recorded in soft soils are used. The energy reduction factors yield inelastic energy spectra that capture in a reasonable manner the energy content of narrow-banded ground motions, and yield a better characterization of inelastic energy demands. Highlights: A study on energy reduction factors for narrow-banded motions is presented. The inelastic input energy spectra is established from energy reduction factor. The hysteretic energy spectra is established from energy reduction factor. Elastic input energy spectra were used as basis of functional forms. A database over 250 seismic records in soft soils was used.